Eruption of the permanent upper canine: A radiologic study - FERNANDEZ, E; BRAVO, L; CANTERAS, M (American journal of orthodontics and dentofacial orthopedics, 1998)
The early detection of eruptive anomalies of the upper canine requires an understanding of its normal eruptive pattern. We studied this pattern in terms of upper canine inclination and its relation to the lateral incisor, on the basis of the panoramic radiographic records of 305 children aged 4 to 12 years. The study sample comprised 554 maxillary canines in the oral pre-emergence phase of eruption. Subject age, sex, inclination of the canine (CI), its relation to the lateral incisor (RCLI), and development of the lateral incisor (DLI) were evaluated. The results show that the canine erupts, increasing its inclination mesially until a maximum is reached, at about 9 years of age, after which the tooth begins to progressively upright itself. The individual variability of the degree of CI at a given age is considerable. In the initial stages, the RCLI is most commonly characterized by overlapping, a situation rarely seen in the final stages. The DLI effectively discriminates both periods, because when DLI is incomplete, more than half of the cases have an overlapping RCLI. In contrast, when the DLI is complete, this overlapping is seen in only 7% to 11% of the cases. This variable therefore increases the capacity to detect a possible eruptive anomaly at an early stage. In patients with complete DLI and overlapping RCLI, particularly when associated with other clinical signs such as the nonpalpation of the cuspid bulge in the alveolar process, the presence of dental agenesis, ankylosis, malformations, or ectopic eruptions, extraction of the primary canine is advised to prevent impaction.